(untitled) (Journal of Pharmaceutical Negative Results, 2022)
IgA Pemphigus is a very rare form of pemphigus characterized by pruritic vesiculopustular eruptions with autoantibodies directed against desmosomes of keratinocytes. The disease is commonly associated with monoclonal IgA gammopathy, B-cell lymphoma, Inflammatory bowel disease, HIV infection and thiol drugs. Here we describe a case of IgA pemphigus associated with supraglottic squamous cell carcinoma. Tzanck smear showed acantholytic cells. Skin biopsy showed intraepidermal blister with mixed neutrophilic and eosinophilic infiltrates. On performing enzyme linked immunosorbent assay (ELISA), IgA autoantibodies reacted to desmocollin 1 antigen. On video laryngoscopy, an ulceroproliferative growth of size 2.3 x 1.6 x 4 cm cm is seen obliterating the left pyriform fossa in the supraglottis. All above results were correlated and a diagnosis of IgA Pemphigus associated with Supraglottic Squamous Carcinoma was made. To the best of our knowledge, no similar association has been reported so far.